AI-writing tools in education: if you can’t beat them, join them - Tseng Waverly; Warschauer Mark (Journal of China Computer-Assisted Language Learning)
The release and rapid diffusion of ChatGPT has forced teachers and researchers around the world to grapple with the consequences of artificial intelligence (AI) for education. For second language educators, AI-generated writing tools such as ChatGPT present special challenges that must be addressed to better support learners. We propose a five-part pedagogical framework that seeks to support second language learners through acknowledging both the immediate and long-term contexts in which we must teach students about these tools: understand, access, prompt, corroborate, and incorporate. By teaching our students how to effectively partner with AI, we can better prepare them for the changing landscape of technology use in the world beyond the classroom.